Effectiveness of Physiotherapy Intervention on the Quality of Life of Women with Breast Cancer who Underwent Sentinel Lymph Node Biopsy. - Duarte, Nuno Miguel; Aguiar, Pedro; Faria, Paula Lobato; Bernardo, Mario (Open Science Journal, 2017)
Purpose: To evaluate if physiotherapy can contribute to the quality of service provided to Women with Breast Cancer who underwent sentinel lymph node biopsy (SLNB). Methods: This Quasi-experimental study addressed a sample of 172 women with breast cancer who underwent surgery with SLNB, 90 were included in the control group and 82 in the experimental group. We used the EORTC C30 and BR23 questionnaires to collect data about the quality of life (QoL) in the course of the first 9 months after surgery. The experimental group was submitted to specific physiotherapy techniques while the control group was the target of assessments only. Poisson regression was used to perform the calculation of the Relative Benefit (aRB) and Relative Risk (aRR) adjusted for several confounding factors at the baseline of the study. Results: In the third month after surgery the experimental group showed a higher proportion of patients with substantial clinical improvement in the Global Health Status (GHS) (aRB=2.230; p=0.014) and a lower risk of degradation of the GHS (aRR=0.384; p=0.011), Physical Function (PF) (aRR=0.484; p=0.035), and Arm Symptoms (BRAS) (aRR=0.159; p=0.007), when compared to the control group. Between the 1st and 6th month after surgery, physiotherapy seems to act as a protective factor on the degradation of GHS and PF. Between the 1st and 9th month after surgery the experimental group showed a higher proportion of patients with notable clinical improvement in the GHS (aRB=1.905; p=0.038) and in the BRAS (aRB=1.761; p=0.029) and a lower risk of degradation of the GHS (aRR=0.287; p=0.010) and BRAS (aRR=0.265; p=0.0421) scales. Conclusions: In the course of the acute survival phase, physiotherapy can help to improve the QoL of women with breast cancer who underwent surgeries with SLNB, giving a positive contribution to the quality of service provided to this group of patients.